Pulmonary hypertension in end-stage renal disease and post renal transplantation patients - Alhamad, Esam H.; Al-Ghonaim, Mohammed; Alfaleh, Hussam F.; Cal, Joseph P.; Said, Nazmi (Journal of Thoracic Disease, 2014)
Background: Information regarding lung function parameters and functional capacity in renal failure and post renal transplantation patients with pulmonary hypertension (PH) is limited. The purpose of this study was to examine the clinical characteristics of patients with PH who were receiving hemodialysis (HD) or peritoneal dialysis (PD) or who had undergone renal transplantation. Methods: A prospective study was performed on 116 patients (HD =55, PD =17, and post renal transplantation =44) who underwent Doppler echocardiography. PH was defined as systolic pulmonary artery pressure (SPAP) ≥40 mmHg. Demographic information, clinical characteristics, pulmonary function tests (PFTs) and the six-minute walk test (6MWT) were collected and compared between the patients with and without PH. Results: Twelve (21.8%) patients receiving HD, four (23.5%) patients receiving PD, and eight (18.2%) post renal transplantation patients had PH. In the HD group, the physiological indicators (including pulmonary function test parameters, the final Borg score, and walking distance during the 6MWT) were all significantly lower in the patients with PH compared with those without PH (all P0.05). Conclusions: Among HD patients, marked aberrations in PFT results or walking distance may identify a subset of patients suffering from PH.